2015
DOI: 10.1111/j.1751-908x.2015.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Ion Mass Spectrometry Bias on Isotope Ratios in Dolomite–Ankerite, Part I: δ18O Matrix Effects

Abstract: We document the development of a suite of carbonate mineral reference materials for calibrating SIMS determinations of δ18O in samples with compositions along the dolomite–ankerite solid solution series [CaMg(CO3)2–CaFe(CO3)2]. Under routine operating conditions for the analysis of carbonates for δ18O with a CAMECA IMS 1280 instrument (at WiscSIMS, University of Wisconsin‐Madison), the magnitude of instrumental bias along the dolomite–ankerite series decreased exponentially by ~ 10‰ with increasing Fe content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…15a, b, c). Notably, this characteristic behaviour of IMF vs. the electrostatic deflectors was also observed in the response surface models fitted using the previously published SIMS data of Śliwiński et al 15 on dolomite-ankerite and Pollington et al…”
Section: Lt1defx-lt1defy Electrostatic Deflectors Peres Et Alsupporting
confidence: 72%
See 2 more Smart Citations
“…15a, b, c). Notably, this characteristic behaviour of IMF vs. the electrostatic deflectors was also observed in the response surface models fitted using the previously published SIMS data of Śliwiński et al 15 on dolomite-ankerite and Pollington et al…”
Section: Lt1defx-lt1defy Electrostatic Deflectors Peres Et Alsupporting
confidence: 72%
“…14c, d), both using a Cameca 1280HR (WiscSims). 15,46 Unexpectedly, the variations observed along Y were slightly negative parabolic or linear with low slopes in all the cases, indicating that the variation of IMF along X is much stronger than along Y. In addition, this behaviour is independent of the value ranges of X, Y, and IMF (Fig.…”
Section: And Y Mount Locationmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, Page et al (2010), found more complicated O-isotope matrix effects in garnet where sputter rate was not correlated with the magnitude of instrumental mass fractionation. Matrix effects in carbonates are also complicated (e.g., Rollion-Bard and Marin-Carbonne, 2011;Śliwiński et al, 2016a, 2016b) although Śliwiński and colleagues were able to fit the IMF data as a function of Fe / (Fe + Mg) content of the carbonates along the dolomite -ankerite solid solution to a Hill equation, which has a similar functional form to the sigmoid that we used relating change in IMF to sputter rate in olivine.…”
Section: Relationship To Sputter Ratementioning
confidence: 99%
“…14 Śliwiński et al correlated the Fe content with bias variation in 18 O/ 16 O and 13 C/ 12 C analyses of the dolomite-ankerite solid solution series using the Hill's equation for nonlinear effects. 15,16 Introduced by Box and Wilson, RSM has been applied to build up multivariate statistical models in a wide variety of industrial, engineering and experimental processes. 17 Successful RSM applications can be found in, e.g., Riley [18][19][20][21][22][23][24][25][26][27][28][29][30] In addition, the mathematical and statistical aspects of RSM and related experimental techniques are covered in e.g., Box, Box, and [31][32][33][34][35][36][37] Simultaneously, the statistical prediction models have been recognized as powerful tools for e.g., exploring the underlying causal relationships below the datasets, building and/or assessing new knowledge and improving previous models.…”
Section: Introductionmentioning
confidence: 99%